The Influence of Education, Training, and Individual Characteristics on The Performance of Civil Servants in State Administrative Institutions - Lorenta, Meta; Krisnandi, Herry; Digdowiseiso, Kumba (Ridwan Institute, 2024)
This study aims to explore the influence of education, training, and individual characteristics on the performance of civil servants within state administration institutions, focusing on a sample of 101 employees randomly selected from the population of 135 at the Jakarta State Administration Institute. This research is included in quantitative research, where the research instrument uses a questionnaire. Utilizing the